Relation between Body Mass Index and Knee Osteoarthritis in Pre-Elderly to Elderly at Orthopedic Poly of Dr. Mohamad Soewandhie Regional Public Hospital Surabaya - Yoga Prana Putra Santosa; Minarni Wartiningsih; Bimo Sasono (International Journal of Advanced Health Science and Technology, 2024)
Osteoarthritis is a degenerative joint disease characterized by painful joints, particularly prevalent in older individuals, attributed to mild inflammation resulting from bone-end friction. A study conducted in Surakarta revealed a 4.9-fold increase in osteoarthritis risk among individuals with a BMI >25 compared to those with a BMI of 18.5-25.0. This research aims to investigate the association between knee osteoarthritis and BMI among elderly patients at the orthopedic outpatient clinic of Sesyapdhio Hospital, Surabaya. Using cross-sectional observational analysis, osteoarthritis patients were identified. The findings indicate a correlation between higher BMI and increased severity of osteoarthritis, contrasting with milder cases observed in individuals with normal BMI. Spearman's rank correlation review revealed a strong positive correlation (r=0.554) between BMI and osteoarthritis severity at Sexygandhio Hospital Surabaya. This study's unique contribution lies in its focused exploration of the relationship between BMI and osteoarthritis severity in elderly patients, offering insights into potential interventions tailored to BMI-specific risk profiles.